A NEW RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE SIMULTANEOUS ESTIMATION OF KETOROLAC TROMETHAMINE AND TRAMADOL HYDROCHLORIDE IN PHARMACEUTICAL DOSAGE FORMS. - Y, Bharathi Devi; Sumanth ks; V, Bhaskara Raju; B, Mohan Gandhi; K, Srinivas (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was embarked upon to develop a new, simple, rapid, validated reversed-phase high-performance liquid chromatography (HPLC) method for the estimation of ketorolac tromethamine (KET) and tramadol hydrochloride (TDL) in pharmaceutical dosage forms. Methods: The HPLC method was developed on Shishiedo C18 column (250 mm Ã— 4.6 mm i.d, 5 Î¼) using methanol: 50 mM phosphate buffer (pH 6.0) in the ratio of 52:48 at 282 nm. Results: Retention time for the drugs was found to be 5.1 and 6.9 minutes for tramadol and ketorolac, respectively. The limit of detection for tramadol and ketorolac were found to be 1.0 and 0.1 Î¼g/ml, limit of quantitation for tramadol and ketorolac were found to be 5.0 and 0.5 Î¼g/ml, respectively. Linearity was established in the range of 20.0-30.0 Î¼g/ml and 8.0-12.0 Î¼g/ml for TDL and KET, respectively. The method was precise with % relative standard deviation <2 for both intra- and interday precision. The accuracy of the method was performed over three levels of concentration, and the recovery was in the range of 98-102%. Conclusion: From the found experimental data, it can be concluded that the developed method is accurate, precise, and selective and can be employed successfully for the estimation of KET and TDL in Pharmaceutical dosage forms. Â 